Osteopontin Promotes Hepatic Progenitor Cell Expansion and Tumorigenicity via Activation of β‐Catenin in Mice. (23rd June 2015) - Liu, Yingying; Cao, Lei; Chen, Rui; Zhou, Xuyu; Fan, Xiaoyu; Liang, Yingchao; Jia, Rongjie; Wang, Hao; Liu, Guoke; Guo, Yajun; Zhao, Jian
Abstract: Upregulation of osteopontin (OPN) has been found in hepatic progenitor cells (HPCs) in several liver diseases with portal biliary proliferation. Here, we investigated the role of HPC‐derived autocrine OPN in regulating HPC expansion, migration, and hepatocarcinogenesis in mice. Five‐week‐old, weighing between 18 and 20 g of either wild type (WT) or OPN gene knockout ( OPN ‐KO) male mice were treated with modified choline‐deficient, ethionine‐supplemented diet (modified choline‐deficient [MCDE]) for 2 weeks to induce HPC production, or 6–12 months to induce tumorigenesis. Epithelial cell adhesion molecule EpCAM + CD45 − cells isolated from mouse liver and liver epithelial progenitor cells were used for in vitro study. OPN was blocked by specific antibody or RNAi‐mediated silence to investigate the role of OPN. To evaluate correlation between OPN expression and β‐catenin activity, expressions of OPN and β‐catenin were assessed in human liver cancer specimens. We found autocrine OPN promotes HPC expansion and migration by decreasing membranous E‐cadherin and increasing free cytoplasmic β‐catenin via binding to αv integrin and activating Src activity. Depletion of OPN significantly attenuated MCDE‐induced hepatocarcinogenesis. Clinical evidence revealed a strong correlation of high OPN expression with cytoplasmic/nuclear expression of β‐catenin in 43 cases of human combined hepatocellular carcinoma and cholangiocarcinoma and mixed intrahepatic cholangiocarcinoma and 80 cases of hepatocellular carcinoma. Our results indicate that autocrine OPN plays a crucial role in HPC expansion, migration, and subsequent oncogenic transformation of HPCs, which may provide a new insight into hepatocarcinogenesis. Stem Cells   2015;33:3569–3580